Hubungan Antara Kecerdasan Spiritual Dengan Kematangan Karir Pada Mahasiswa - Islamiyah, Salimatul; Murni, Sheila Natasha; Faizah, Yusra (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The background of this research is low career maturity or career immaturity among students, the ability to plan a career is still a problem where emotional intelligence is also needed to overcome the problems faced by prospective new graduates such as worry and fear of not getting a job, feeling a lack of information. a job and feel unable to adapt to a job. The aim of this research is to determine the relationship between emotional intelligence and career maturity in students. The research method uses quantitative and the sampling method used in this research is a simple random sampling technique. The population of this study were students from several universities. The total research sample was 30 people. The results based on the calculation of the hypothesis test t = 5.29057 are then consulted with dk = n (number of samples) - k (number of variables), namely the sample number is 30-2 = 28 and the 5% significance level is known to be t table = 2.048 so that the t count >t table 5.29057 >2.048, thus Ho is rejected and Ha is accepted. This shows that there is a very significant correlation between spiritual intelligence and career maturity in students at several universities. This means that having high spiritual intelligence will also be followed by having high career maturity. Vice versa, having low emotional intelligence will also be followed by low careerÂ maturity.